2015
DOI: 10.1016/j.jamcollsurg.2014.12.025
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prognostic Nomogram Accurately Predicts Hepatocellular Carcinoma Recurrence after Liver Transplantation: Analysis of 865 Consecutive Liver Transplant Recipients

Abstract: Background: While radiological size criteria(Milan/UCSF) have led to improved outcomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
180
5
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 218 publications
(208 citation statements)
references
References 56 publications
(31 reference statements)
19
180
5
4
Order By: Relevance
“…To evaluate the predictive accuracy of a nomogram, the C-index is widely used. The bootstrap-corrected C-index for the nomogram formulated in the present study was 0.77, which is comparable or higher than those of past studies, [33][34][35][36][37][38] suggesting the high accuracy of our nomogram for predicting 6-month survival rates. Therefore, in a heterogeneous group of patients with HCC who are referred for RT to LN metastasis, this nomogram can be used effectively to predict survival outcomes.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…To evaluate the predictive accuracy of a nomogram, the C-index is widely used. The bootstrap-corrected C-index for the nomogram formulated in the present study was 0.77, which is comparable or higher than those of past studies, [33][34][35][36][37][38] suggesting the high accuracy of our nomogram for predicting 6-month survival rates. Therefore, in a heterogeneous group of patients with HCC who are referred for RT to LN metastasis, this nomogram can be used effectively to predict survival outcomes.…”
Section: Discussionsupporting
confidence: 81%
“…19,27,28,[32][33][34][35][36][37][38] However, in patients undergoing RT for LN metastasis, no prognostic grouping or nomogram has been suggested for use. In our study, a prognostic grouping by the number of risk factors was formulated based on the results of multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular invasion is associated with a high potential for recurrence after resection of HCC. 2,3,16,26 However, the impact of mVI and resection margin in the PR specimen on the outcome of IHR management has not been widely studied.…”
mentioning
confidence: 99%
“…In these studies, the explanted liver in the transplant setting rather than the previously resected HCC was the key factor to predict tumor recurrence. 26,27 Meniconi et al suggested that SLT should not be performed in patients where HCC was observed in the PR with mVI. 28 However, this study did not investigate the impact of mVI in PR on the outcome of SLT.…”
mentioning
confidence: 99%
“…No patients in that study who had an elevated NLR survived to 3 years (42). Another large study of patients with LT for HCC noted that as NLR increased each log unit, the risk of HCC recurrence nearly doubled (41). Not only has NLR been demonstrated to be predictive of survival in patients undergoing LT for HCC, it has been successful in evaluating patients undergoing tumor downstaging procedures such as radiofrequency ablation (RFA) (44)(45)(46) and transcatheter arterial chemoembolization (TACE) (47).…”
Section: Neutrophil Lymphocyte Ratio (Nlr)mentioning
confidence: 99%